2011
DOI: 10.1073/pnas.1117298108
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a biofilm electrocline using real-time 3D metabolite analysis

Abstract: Bacteria are social organisms that possess multiple pathways for sensing and responding to small molecules produced by other microbes. Most bacteria in nature exist in sessile communities called biofilms, and the ability of biofilm bacteria to sense and respond to small molecule signals and cues produced by neighboring biofilm bacteria is particularly important. To understand microbial interactions between biofilms, it is necessary to perform rapid, real-time spatial quantification of small molecules in microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
100
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 42 publications
2
100
0
Order By: Relevance
“…Several reviews have been dedicated to SECM investigations of such biological systems. [119][120][121][122][123] More recent applications have involved assessing multidrug resistance on cell co-culture patterns, 124 real-time mapping of local hydrogen peroxide production across a biofilm of oral bacteria and in observing its consumption in a polymicrobial biofilm through a mechanism involving one of the bacteria during spatial scanning, 125 in the discovery of a biofilm electrocline of oral bacteria using real-time 3D metabolite analysis, 126 and in the real-time monitoring of quorum sensing in bacterial aggregates. 127,128 Some examples are briefly discussed below.…”
Section: Secm Investigations In Biological Systemsmentioning
confidence: 99%
“…Several reviews have been dedicated to SECM investigations of such biological systems. [119][120][121][122][123] More recent applications have involved assessing multidrug resistance on cell co-culture patterns, 124 real-time mapping of local hydrogen peroxide production across a biofilm of oral bacteria and in observing its consumption in a polymicrobial biofilm through a mechanism involving one of the bacteria during spatial scanning, 125 in the discovery of a biofilm electrocline of oral bacteria using real-time 3D metabolite analysis, 126 and in the real-time monitoring of quorum sensing in bacterial aggregates. 127,128 Some examples are briefly discussed below.…”
Section: Secm Investigations In Biological Systemsmentioning
confidence: 99%
“…Recently, it was shown that phenazine carboxylic acid can promote P. aeruginosa biofilm formation by stimulating Fe(II) acquisition in the presence of conalbumin (61). In addition, the presence of Fe(II) has been detected within a P. aeruginosa biofilm producing a gradient of the reduced phenazine pyocyanin (25).…”
mentioning
confidence: 99%
“…In particular, Koley showed that a reduced layer of pyocyanin exists for 500 m above a Pseudomonas biofilm, even in the presence of oxygen. This may be critical to the organism's ability to scavenge iron (32). The SECM approach enables quantitative measurements of redox metabolite production in real time and in three dimensions (3D) that will undoubtedly facilitate a better understanding of how they aid bacterial survival and growth.…”
Section: Part 2 New Discoveries About Signaling Pathwaysmentioning
confidence: 99%